Head and neck cancer patient images for determining auto‐segmentation accuracy in T2‐weighted magnetic resonance imaging through expert manual segmentations. Issue 12 (1st March 2021) - Cardenas, Carlos E.; Mohamed, Abdallah S. R.; Yang, Jinzhong; Gooding, Mark; Veeraraghavan, Harini; Kalpathy-Cramer, Jayashree; Ping Ng, Sweet; Ding, Yao; Wang, Jihong; Lai, Stephen Y.; Fuller, Clifton D.; Sharp, Greg
Abstract : Published in Medical Physics, Vol. 47, No. 5